Pengaruh Dosis dan Waktu Aplikasi Pupuk Hijau Lamtoro (Leucaena leucocephala (Lam.) de Wit) terhadap Sifat Kimia Tanah dan Hasil Tanaman Jagung (Zea mays L.) di Suco Mauboke, Distrik Liquiça Timor Leste - IDA PEREIRA DOS SANTOS; NI LUH KARTINI; GEDE WIJANA (Agrotrop : Journal on Agriculture Science, 2017)
The Effect of Dose and Time of Application of Green Manure of Lamtoro (Leucaena leucocephala (Lam.) de Wit) on The Chemical Properties of Soil and Plant Yield of Corn (Zea mays L.) in Village Mauboke, District Of Liquiça East Timor. Corn (Zea mays L.) as food, is a source of carbohydrate both after the rice, besides corn was also used the livestock feed ingredients and raw materials industry. Low crop yields at dryland farming areas is generally associated with poor soil physical and chemical properties. The application of green lamtoro, at appropriate rate and time is expected to be able to improve the soil fertility and in the end to increase crop yields. A Field experiments was conducted atvillage Mauboke, district Liquiça of Timor Leste, to know the effects of rates and time of application green lamtoro on the soil chemical properties and the yield of corn. The experiment was done from February until July 2016. A randomized completed block designwith two factors of treatment arranged factorially, was used in this experiment. The treatment consisted of greenfertilizer lamtoro 5, 10 and 15 tha-1and times of application 1, 2, 3 and 4 weeks before planting. All treatment were replicated three times. Results of experimentindicated that the interaction between rates and time of application of green fertilizer lamtoro real effects of soil N-total, number of plant and extensive index leaf, fresh brangkasanweight plants, brangkasan oven dry weight plants. The heighest oven dry seed weight was also resulted from the same rate 15 tha-1the highest 14,46% wish was not significantly. The time of green fertilizer lamtoro of 4 MST the best improved fertility of soil chemical on the rate of 15 tha-1 with the increase of C-organic of 37,90% lowest 20,93%, P-available 76,27% lowest 26.58%, K-available 100,79% lowest 21,35%. The best rate ofgreenfertilizerlamtoro 15 tha-1highest 3.7 tha-1shelled dry. The soil with similar soil condition with that ofthe experimentrecommended that the utilizing of rate green fertilizer lamtoro 15 tha-1with time application of 4 MST the increased production of corn crops.